2020
DOI: 10.1002/cplu.202000620
|View full text |Cite
|
Sign up to set email alerts
|

(N),C,N‐Coordinated Heavier Group 13–15 Compounds: Synthesis, Structure and Applications

Abstract: The aim of this review is to summarize recent achievements in the field of (N),C,N‐coordinated group 13–15 compounds not only regarding their synthesis and structure, but mainly focusing on their potential applications. Relevant compounds contain various types of N‐coordinating ligands built up on an ortho‐(di)substituted phenyl platform. Thus, group 13 and 14 derivatives were used as single‐source precursors for the deposition of semiconducting thin films, as building blocks for the preparation of high‐molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 117 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…11–15 Over time, aryl ligands with nitrogen pincer arms have afforded remarkable antimony and bismuth synthons for further unusual reactivity studies. 16,17 In this regard, our work revealed that NCN-pincer ligands, e.g. 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 and 2,6-{MeN(CH 2 CH 2 ) 2 NCH 2 } 2 C 6 H 3 with sp 3 nitrogen as donor atoms, can provide a satisfactory ligand environment for the synthesis of low oxidation state organobismuth species, 18 arylpnictogen( iii ) carbonates, 19,20 the first peroxo R 1 2 Bi–O–O–BiR 1 2 [R 1 = 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 ] derivative, 18 and hypercoordinated monoorganopnictogen( iii ) oxides.…”
Section: Introductionmentioning
confidence: 81%
“…11–15 Over time, aryl ligands with nitrogen pincer arms have afforded remarkable antimony and bismuth synthons for further unusual reactivity studies. 16,17 In this regard, our work revealed that NCN-pincer ligands, e.g. 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 and 2,6-{MeN(CH 2 CH 2 ) 2 NCH 2 } 2 C 6 H 3 with sp 3 nitrogen as donor atoms, can provide a satisfactory ligand environment for the synthesis of low oxidation state organobismuth species, 18 arylpnictogen( iii ) carbonates, 19,20 the first peroxo R 1 2 Bi–O–O–BiR 1 2 [R 1 = 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 ] derivative, 18 and hypercoordinated monoorganopnictogen( iii ) oxides.…”
Section: Introductionmentioning
confidence: 81%
“…[2e,8,9] Due to their potential application and unprecedented bonding nature, there is always a quest to synthesize the new chalcogenides (Chart 1). [3,[6][7][8][9] The synthesis of these heavy ketones is very much dependent upon the bulkiness of the substituents as an increase in bulk favors the stabilization of double-bonded compounds (Ge/ Sn = X, X = S, Se, Te), while the decrease in the bulk furnishes cyclic E 2 X 2 moiety (E = Ge, Sn; X = S, Se, Te). [10,11] In order to synthesize the double-bonded chalcogenides, we utilized a bulky ligand 1 ((E)-1-(2-bromophenyl)-N-(2,6-dibenzhydryl-4methylphenyl)ethan-1-imine) with a sterically crowded Ar* group [Ar* = 2,6-(dibenzhydryl-4-methylphenyl] on the nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] In order to synthesize the double-bonded chalcogenides, we utilized a bulky ligand 1 ((E)-1-(2-bromophenyl)-N-(2,6-dibenzhydryl-4methylphenyl)ethan-1-imine) with a sterically crowded Ar* group [Ar* = 2,6-(dibenzhydryl-4-methylphenyl] on the nitrogen atom. [12] Herein, we report sterically demanding chlorogermylene (2), chlorostannylene (3), homoleptic germylene (4), homoleptic stannylene (5), germaselenone (7), stannaselenone (8), and stannatellurone (9). All the compounds were studied by the multinuclear NMR and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations